The Armenian Four Gospels of the Russian State Library (f. 439.23.5): the Attribution of the Miniatures - Danielyan, Inesa G. (Actual Problems of Theory and History of Art, 2017)
The article is devoted to the study of the miniatures of the Armenian Four Gospels from the manuscript collection of Russian State Library (f. 439.23.5). The illustrations of the manuscript consist of canontables (khorans), portraits of the Evangelists, title pages, and marginalias. The author, the date, and the place of the creation of the Gospels are unknown, as the last pages, where the main information about a manuscript is usually put down, were lost. The article discusses the question of the authorship of the manuscript art work. The portraits of the evangelists demonstrate close similarity with Momik’s manuscript of 1302 (Yerevan, Matenadaran,№ 6792). Based on the stylistic and iconographic study of the miniatures, we consider that it was Momik who illustrated the Gospels f. 439.23.5. The codex can be dated to the first decade of the 14th century. It is possible that the patrons of the manuscript were the Orbelians, one of the most significant feudal families of the time, as master Momik generally worked under their patronage.
Keywords: Мomik; Gospels; Russian State Library; Armenian miniature; Evangelists